Disintegration of chemotherapy tablets for oral administration in patients with swallowing difficulties. (June 2013) - Siden, Rivka; Wolf, Matthew
Purpose: The administration of oral chemotherapeutic drugs can be problematic in patients with swallowing difficulties. Inability to swallow solid dosage forms can compromise compliance and may lead to poor clinical outcome. The current technique of tablet crushing to aid in administration is considered an unsafe practice. By developing a technique to disintegrate tablets in an oral syringe, the risk associated with tablet crushing can be avoided. The purpose of this study was to determine the feasibility of using disintegration in an oral syringe for the administration of oral chemotherapeutic tablets. Eight commonly used oral chemotherapeutic drugs were tested. Methods: Tablets were placed in an oral syringe and allowed to disintegrate in tap water. Various volumes and temperatures were tested to identify which combination allows for complete disintegration of the tablet in the shortest amount of time. The oral syringe disintegration method was considered feasible if disintegration occurred in£ ≤15 min and in ≤£ 20 mL of water and the dispersion passed through an oral syringe tip. Results: The following tablets were shown to disintegrate within 15 min and in <20 mL of water: busulfan, cyclophosphamide 50 mg, dasatinib, imatinib, methotrexate, and thioguanine. For these drugs, drug-specific information pamphlets can be prepared for patient or caregiver use. Mercaptopurine, cyclophosphamide 25 mg, and mitotane tablets did not pass the disintegration test. Conclusion: Disintegrating oral chemotherapeutic tablets in a syringe provides a closed system to administer hazardous drugs and allows for the safe administration of oral chemotherapeutic drugs in a tablet form to patients with swallowing difficulties.